Pengaruh Lingkungan Kerja dan Pemberian Insentif Terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi: Studi pada Karyawan Bank XXX cabang Semarang) - Husni Aufar Hakim; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2025)
Employee performance is a key factor that influences the success of an organization, especially in the era of digitalization and increasingly fierce business competition. A conducive work environment and appropriate incentives have a significant impact on employee performance. This study aims to examine the influence of the work environment and incentives on employee performance, with job satisfaction as a mediating variable. This study seeks to address the inconsistencies in the research gaps of previous studies, particularly in exploring and developing a conceptual framework that involves key variables such as work environment, incentives, job satisfaction, and employee performance.The population of this study consists of all active employees of Bank BNI Semarang Branch. A sample of 126 respondents was obtained through the distribution of questionnaires. The collected data were then analyzed quantitatively using Structural Equation Modeling (SEM) with AMOS version 24 software.The findings of this study show that the work environment has a positive effect on employee performance. Furthermore, the incentive variable also has a positive and significant effect on employee performance. The mediation test results indicate that the relationship between the work environment and incentives on performance can be strengthened by the mediation of job satisfaction, making its effect positive and significant.